DYNAMICAL SYSTEM ON TOPOLOGICAL STRUCTURE OF SET F(SxT,X) - Dervishi, Neki (Matematichki Bilten, 2007)
In this paper is proved that, if \(T\) is a Hausdorff topological abelian group, and if \(Y\) is a Hausdorff topological space, then the mapping \(φ(f,t)=f_t\), defines a general and continuous dynamical system on topological structure of set \(F(S × T,X)\), relative to the relative topology of coordinatewise convergence.